DIGITAL LITERACY DEVELOPMENT: ASSESSING THE EFFICACY OF ONLINE LEARNING PLATFORMS IN ENHANCING STUDENTS' INFORMATION FLUENCY - Reyaz Ahmad Bhat (RADJA PUBLIKA, 2023)
Abstract Digital literacy is a critical skill in today's information-rich society. This research paper investigates the impact of online learning platforms on students' information fluency—a crucial component of digital literacy. The study evaluates the effectiveness of various online tools and resources in improving students' abilities to locate, evaluate, and synthesize digital information. Through a comprehensive assessment and analysis, the paper aims to contribute valuable insights to the field of education and technology-enhanced learning. Key words: Digital literacy, technology –enhanced learnin